Pyrrosia serpens (G.Forst.) Ching a new record for the fern flora of the Kermadec Islands. Issue 2 (3rd April 2021) - Brownsey, Patrick; Shepherd, Lara; de Lange, Peter; Perrie, Leon
ABSTRACT: Pyrrosia serpens is recorded here for the first time from the New Zealand Botanical Region, based on a single collection from Dayrell Island in the Kermadec Islands. This is a significant southern extension of range for the species, otherwise known in the Pacific from Fiji to Pitcairn and Henderson Islands. The identification of the Dayrell Island collection is based on evidence from both morphology (particularly soral and rhizome scale characters) and genetics. Morphological comparisons were made, in particular, with three related Australasian species. Phylogenetic analysis shows that the chloroplast DNA sequence of the Dayrell Island collection is very similar to that of P. serpens from the Cook Islands. However, previously reported sequences from samples of P. serpens from elsewhere are very different, reflecting a wider need for further taxonomic investigation of Pyrrosia subgenus Nipholobus . Pyrrosia serpens is one of ten fern species that, in New Zealand, are found only on the Kermadec Islands. In preparation for a revised treatment of Polypodiaceae for the electronic Flora of New Zealand, the taxonomic treatment of Pyrrosia is reviewed, a description of P. serpens from the Kermadec Islands provided, and its conservation status assessed.